KAJIAN FILSAFAT ILMU TERHADAP PENDEKATAN PROJECT-BASED LEARNING DALAM PENGEMBANGAN LITERASI SAINS PADA IMPLEMENTASI KURIKULUM MERDEKA - Saifudin, Muhammad Fakhri (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2026)
This study philosophically analyzes the Project-Based Learning (PjBL) approach as the primary method in science development in the Independent Curriculum, particularly in the context of improving students' scientific literacy. The Independent Curriculum encourages student-centered and contextual learning, in line with the demands of contemporary philosophy of science that emphasizes the practical aspects and relevance of knowledge to real life. The research method used is a philosophical-qualitative analysis with a critical literature study approach. The analysis was conducted to understand the paradigm shift from science learning that is knowledge transmission (positivistic) to science learning as a process of discovery and meaning (constructivist) through PjBL. This philosophical study of science concludes that the implementation of PjBL is a progressive step in science education in Indonesia, leading to a more holistic, relevant, and meaningful understanding of science for students.